2018
DOI: 10.1364/boe.9.001082
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field quantitative micro-elastography of human breast tissue

Abstract: Currently, 20-30% of patients undergoing breast-conserving surgery require a second surgery due to insufficient surgical margins in the initial procedure. We have developed a wide-field quantitative micro-elastography system for the assessment of tumor margins. In this technique, we map tissue elasticity over a field-of-view of ~46 × 46 mm. We performed wide-field quantitative micro-elastography on thirteen specimens of freshly excised tissue acquired from patients undergoing mastectomy. We present wide-field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Statistical analysis performed in this study has shown that tumor exhibits median stress of 60 kPa, higher than that of adipose and stroma, in cases when the preload was controlled between 15% and 25%. The elevated stress, which is sensitive to the underlying elasticity of features in tissue, measured for invasive tumor in this study is consistent with QME studies; where it was shown that invasive tumor exhibits elevated elasticity in comparison to benign dense tissue . Stress is a qualitative measurement; therefore, the measured stress in the layer is proportional to the preload applied.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Statistical analysis performed in this study has shown that tumor exhibits median stress of 60 kPa, higher than that of adipose and stroma, in cases when the preload was controlled between 15% and 25%. The elevated stress, which is sensitive to the underlying elasticity of features in tissue, measured for invasive tumor in this study is consistent with QME studies; where it was shown that invasive tumor exhibits elevated elasticity in comparison to benign dense tissue . Stress is a qualitative measurement; therefore, the measured stress in the layer is proportional to the preload applied.…”
Section: Discussionsupporting
confidence: 89%
“…Finally, we anticipate that by mimicking the sense of touch, a tool that surgeons routinely use to assess tissue, optical palpation may provide images that can prove more intuitive to interpret than other forms of intraoperative imaging. However, the significant advantages of QME over optical palpation are the quantification of elasticity , the ability to perform depth sectioning of mechanical contrast, up to ~1 mm , and higher spatial resolution (which is discussed in the Supporting Information in Appendix S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations